Maternal depression from early pregnancy to 4 years postpartum in a prospective pregnancy cohort study: implications for primary health care. (21st May 2014) - Woolhouse, H; Gartland, D; Mensah, F; Brown, SJ
<x xml:space="preserve">Abstract</x> Objective To describe the prevalence of maternal depression from pregnancy to 4 years postpartum, and the risk factors for depressive symptoms at 4 years postpartum. Design Prospective pregnancy cohort study of nulliparous women. Setting Melbourne, Australia. Sample In all, 1507 women completed baseline data in pregnancy (mean gestation 15 weeks). Methods Women were recruited from six public hospitals. Questionnaires were completed at recruitment and 3, 6, 12 and 18 months postpartum, and 4 years postpartum. Main outcome measures Scores ≥13 on the Edinburgh Postnatal Depression Scale were used to indicate depressive symptoms. Results Almost one in three women reported depressive symptoms at least once in the first 4 years after birth. The prevalence of depressive symptoms at 4 years postpartum was 14.5%, and was higher than at any time‐point in the first 12 months postpartum. Women with one child at 4 years postpartum were more likely to report depressive symptoms at this time compared with women with subsequent children (22.9 versus 11.3%), and this association remained significant in adjusted models (Adjusted odds ratio 1.71, 95% confidence interval 1.12–2.63). Conclusions Maternal depression is more common at 4 years postpartum than at any time in the first 12 months postpartum, and women with one child at 4 years postpartum report significantly higher levels of depressive symptoms than women with subsequent children. There is a need for scaling up of current services to extend surveillance of maternal mental health to cover the early years of parenting.